Cultural Heritage – Theoretical And Practical Aspects Considerations Regarding Its International And Constitutional Regulations - Oana ŞARAMET (Public Administration and Regional Studies (PARS), 2023)
Unlike other beings, human being expresses his thoughts, ideas, values, his own identity or that of the community to which he belongs, also through culture. The preservation of the cultural values that have been transmitted to us by our ancestors and their transmission to our descendants must be considered true fundamental duties related to access to culture, as a fundamental right enshrined in fundamental international and national normative acts. Therefore, in this article, we aim to highlight, but also to make assessments on the international and constitutional regulations that configure the legal framework, at the highest legislative level, regarding the protection and conservation of cultural heritage. On the other hand, we consider it necessary to highlight that sustainable development - a concept, a principle that guides the development of current democratic societies – in no way implies the abandonment of cultural heritage, and achieving the objectives proposed by the 2030 Agenda for Sustainable Development, such as reduced inequalities, or quality education it is not possible by ignoring cultural heritage.
Keywords: heritage; culture; constitution; fundamental right; identity; sustainable development